Study on the Development of Remote Health Monitoring System Based on Internet of Things (IoT) for Patients Integrated with Mobile Application - Prasad, P. P. M.; Kanagasabai, N.; Kumar, P. Surendra (Science and Technology: Recent Updates and Future Prospects Vol. 9, 2024)
Nowadays health monitoring is very important. A lot of changes occur in the human body due to rapid changes in the environment. The Internet of Things (IoT) has enabled incredible attributes in various applications of human health monitoring systems. The IOT-embedded hand-held mobile application technology is a hasty technology to measure the performance of the human health environment. The present study focuses on the practical usage, factors of consuming low power, and real-time system on remote monitoring based on the technology of IoT. This startup has provided an enhanced step in the field of cloud-mode monitoring of health. The assistance of IoT with the systems of wearable sensor technology is one of the emerging fields in healthcare applications. People are spending a lot of money on their health issues. The cluster of population that were availing the requirements for health care monitoring are increasing year by year and the development of standard smart digital intelligent systems that have to be virtually connected with the hospitals. This could formulate an unhealthy circumstance for providing care to the patients who are affected with disease specifically those with unstable and serious disorders. Therefore, the advancement of contemporary electrical and electronic devices that are internet-integrated may offer globally sustainable alternatives. This study uses a smartphone application that operates on the Internet of Things platform to access biological signals for humans, including blood pressure, heart rate, brain frequency, pulse rate, and electrocardiogram (ECG). Measurement and processing of certain symptoms are being utilized with the maximal speed and high memory microcontroller. The primary contribution is to transmit an ECG signal to the cell phone for clinical examination. This assists in diagnosing cardiac disease prior to the serious disorders or hazardous effects to occur for humans. Lastly, the acquired results are built as an output of an Intelligent mobile application. The proposed design is illustrated with proof as very simple and useful to human in proper monitoring of their individual health especially under emergency conditions could easily seek doctors for further medication and treatment. This reduces the risk of death and serious illness.